The Attack of the Rus’ on Constantinople in the Light of the Chronicon Bruxellense - Fylypchuk, Oleksandr (Studia Ceranea, 2022)
The Chronicon Bruxellense does not simply provide useful information on the date of the date (year, month, and day) of the Rus’ attack on the Constantinople (18 June 860), but is crucial for a deeper understanding of nature of this chronicle and his sources. The article reveals important details about the date and structure of the Chronicon Bruxellense. It also offers his sources of description of Rus’ raid and identifies George Monachus Continuatus’s chronicle as the principal model. By seeking to construction the victory over the Rus’, his anonymous author presents as a skilled compiler. This paper engages with recent discussion on the first attack of Rus’ on the Constantinople, while also contributing to the renewed interest in the reception of the Chronicon Bruxellense in the late Byzantine literature.